Protective effects of polysaccharide SH-P-1-1 isolated from Phellinus igniarius on hyperuricemia and gout via intestinal microecosystem regulation - Wang, Yanan; Qian, Xinyi; Chen, Lingzhi; Yang, Ling; Zhang, Zhenjiang; Qu, Zhilong; Yang, Yuhan; Li, Yihao; Ni, Zaizhong; Shao, Ying; Chen, Anhui (Frontiers in Nutrition, 2025)
IntroductionAlthough Phellinus igniarius has been shown to treat hyperuricemia (HUA) and gout, a self-inflammatory disease caused by purine metabolism disorders, the underlying mechanisms remain unclear. Polysaccharides are among the main components of P. igniarius with anti-inflammatory and immunoregulatory properties.MethodsHere, we examined the therapeutic effects of polysaccharide SH-P-1-1 isolated from P. igniarius on HUA and gout, and explored the underlying mechanism, focusing on gut microbiota and metabolite regulation.ResultsSH-P-1-1 significantly decreased uric acid and creatinine levels, reduced xanthine oxidase and adenosine deaminase activities, alleviated kidney damage, and reduced urate deposition in joints in model rats. It increased the abundance of Blautia and Muribaculaceae but reduced that of the Lachnospiraceae_NK4A136_group, Lactobacillus, and Turicibacter. SH-P-1-1 also significantly modulated the metabolic profile and was closely related to some metabolic pathways, such as tryptophan metabolism, relevant to HUA and gout. The beneficial activities of SH-P-1-1 correlated with gut microbiota composition and differential metabolites, including short-chain fatty acids.DiscussionOverall, this study demonstrates the potential of SH-P-1-1 as a natural supplement for preventing and managing HUA and gout.